Divergent Paths of Protestantism and Asian Nationalism: A Comparison of Two Social Movements in Korea and China in 1919 - Ma, Li (International bulletin of mission research, 2018)
In Korea, the March First Movement in 1919 fused Christian identity with nationalistic rituals, making Korean Protestants respectable patriots in the eyes of their countrymen. In China, however, the fledgling nationalism nurtured by the May Fourth Movement in the same year soon gave rise to strong anti-Christian sentiments, culminating in major waves of anti-Christian movements in the 1920s. How do we explain these different outcomes? We argue that the encounters between two different types of Protestantism and two variant forms of nationalism led Korea and China on divergent paths.